2017
DOI: 10.1111/jgh.13663
|View full text |Cite
|
Sign up to set email alerts
|

Real‐life efficacy and safety of paritaprevir/ritonavir, ombitasvir, and dasabuvir in chronic hepatitis C patients in Hong Kong

Abstract: Paritaprevir/ritonavir, ombitasvir, and dasabuvir with or without ribavirin is effective and safe in patients with genotype 1 HCV infection in real-life clinical setting in Hong Kong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 14 publications
3
18
0
Order By: Relevance
“…At week 4 of treatment, the rate of serum HCV RNA level < LLOQ in our patients receiving PrOD‐based regimens was 98.0%, which was much higher than East Asian HCV‐1b patients receiving peginterferon plus RBV. After 12 weeks of off‐therapy follow‐up, the SVR 12 rate in our study was 98.1% and was comparable with the clinical trials and the published real‐world studies for HCV‐1b infected patients receiving the PrOD‐based regimens . In lines with the trial reports, we confirmed that the SVR 12 rates were comparable in our patients receiving PrOD‐based treatment, regardless of sex, age, prior treatment experience, HBsAg status, RBV usage, baseline HCV RNA levels, eGFR or stage of hepatic fibrosis .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…At week 4 of treatment, the rate of serum HCV RNA level < LLOQ in our patients receiving PrOD‐based regimens was 98.0%, which was much higher than East Asian HCV‐1b patients receiving peginterferon plus RBV. After 12 weeks of off‐therapy follow‐up, the SVR 12 rate in our study was 98.1% and was comparable with the clinical trials and the published real‐world studies for HCV‐1b infected patients receiving the PrOD‐based regimens . In lines with the trial reports, we confirmed that the SVR 12 rates were comparable in our patients receiving PrOD‐based treatment, regardless of sex, age, prior treatment experience, HBsAg status, RBV usage, baseline HCV RNA levels, eGFR or stage of hepatic fibrosis .…”
Section: Discussionsupporting
confidence: 89%
“…Regarding the real‐world data of PrOD‐based treatment in Asian patients, one report from Hong Kong evaluated 35 HCV‐1b patients receiving PrOD with or without RBV for 12–24 weeks. The SVR 12 was achieved in 33 of the 35 patients (94.3%) . Two patients who failed to achieve SVR 12 prematurely discontinued treatment due to serious adverse events (AEs).…”
Section: Introductionmentioning
confidence: 99%
“…This is best reflected by very high SVR rates in both compensated and decompensated HCV GT-1 liver cirrhosis patients. Our study is in accordance with previous real-life studies investigating the efficacy of OBV/PTV/r+DSV±RBV in chronic hepatitis C patients [9][10][11][12][17][18][19] with SVR rates between 86% and 100%. In real-life cohorts, patients who failed to achieve SVR were mainly cirrhotics [9][10][17][18].…”
Section: Discussionsupporting
confidence: 79%
“…Also, the discontinuation rate due to serious adverse events occurred only in 0-2% in clinical trials [4][5][6][7][8]. Recent studies from clinical daily experience showed similar excellent SVR rates (93-100%) and good tolerability and safety (discontinuation rate 0-5%) [9][10][11][12]. Achieving SVR in patients with F3-F4 METAVIR fibrosis leads to a lower incidence of cirrhosis-related complications, J Gastrointestin Liver Dis, September 2017 Vol.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 8262 citations and 23 additional manually searched articles evaluated, we included 41 studies published in full articles (Figure ) . Of those, four studies were used only to extract data for subgroup analysis because the overall SVR data were already reported and extracted for overlapping populations in other four included studies .…”
Section: Resultsmentioning
confidence: 99%